Treatment of Schizophrenia Negative Symptoms: Future Prospects - Erhart, Stephen M (Oxford University Press, 2006)
New findings from neuroscience, genetics, and experimental psychology have emerged that provide alternative explanations of many negative symptoms. We review the continuing limitations in treatment and discuss possible sources of heterogeneity among negative symptoms. We also anticipate conceptual uncertainties that may arise with forthcoming treatment developments.